Global, regional, and national estimates of burden and risk factors of female cancers in child-bearing age: A systematic analysis for Global Burden of Disease Study and Bayesian projection to 2030 - Guang Chen; Shichen Zhou; Qiaoxin Shi; Yunqing Xun; Tung-Leong Fong; Ruogu Xiong; Ya Xuan Sun; Junjie Lu; Yige Li; Zheng Li; Guanghui Zhu; Ying Wu; et al. (Translational Oncology)
Background: The prevention, management, and treatment of female cancers among women of childbearing age (WCBA) are crucial strategies for achieving the objectives outlined in the World Health Organization (WHO) Global Breast Cancer Initiative and Cervical Cancer Elimination Initiative. This review aims to provide comprehensive global, regional, and national estimates of the burden of female cancers in women of childbearing age, as well as their attributable risk factors, from 1990 to 2021. Methods: According to the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 methodology, we estimated the incidence, disability-adjusted life-years (DALYs), and mortality of breast, cervical, ovarian, and uterine cancer among women of childbearing age. Temporal trends were assessed using the age-adjusted percentage change (AAPC). Risk factors were estimated using the population attributable fraction, stratified by socio-demographic index (SDI). Projections to 2030 were generated using a Bayesian model. Results: In 2021, the global incidence of breast, uterine, cervical, and ovarian cancer among WCBA was 561,438 (95 % Uncertainty Interval [UI]: 523,147–602,978), 58,860 (95 % UI: 50,765–65,452), 307,428 (95 % UI: 280,667–335,692), and 85,749 (95 % UI: 75,169–95,090), respectively, corresponding to age-standardized rates per 100,000 population of 28.1 (95 % Confidence Interval [CI]: 28.0–28.1), 2.9 (95 % CI: 2.9–3.0), 15.4 (95 % CI: 15.4–15.5), and 4.3 (95 % CI: 4.3–4.4). Breast cancer accounted for the highest number of DALYs at 6659,460 (95 % UI: 6192,226–7145,549), followed by cervical cancer at 4184,314 (95 % UI: 3779,640–4629,604). Diets high in red meat, smoking, and alcohol consumption contributed to 11.2 %, 2.5 %, and 2.6 % of breast cancer deaths, respectively, while unprotected sex accounted for majority of cervical cancer deaths. Obesity was responsible for 30.2 % of both ovarian and uterine cancer deaths. Bayesian projection models indicated that by 2030, the global age-standardized incidence rates of breast and ovarian cancers among WCBA will reach 31.5 and 4.7 per 100,000 population, respectively. Conclusion: Globally, the number of breast, uterine, and ovarian cancer cases among WCBA has increased over the past decade, accompanied by a steady rise in age-standardized incidence rates. In contrast, while the absolute number of cervical cancer cases has risen, its age-standardized incidence rate has declined. Mortality rates for both breast and cervical cancers have generally decreased worldwide; however, in countries within the lower SDI quintile, mortality rates for these cancers continue to rise. Therefore, priority should be given to initiatives such as smoking cessation programs, alcohol reduction strategies, HPV vaccination campaigns, and safe sex education, particularly in lower SDI countries.